PELATIHAN PENERAPAN ALAT PENGASAPAN IKAN TERBANG DI KELURAHAN MOSSO, PROVINSI SULAWESI BARAT - Nur, Muhammad; Ihsan, Muhammad Nur; Ayuandiani, Wulan; Fahrul, Fahrul (Universitas Mataram, 2024)
Mosso Village is a coastal area that produces flying fish in the waters of the Makassar Strait, West Sulawesi Province. This prompted the local government to establish a flying fish processing center at that location. One of the main businesses that is being pushed to become a superior product at the Center is smoking flying fish. The main problem of people smoking flying fish is that people's income and welfare are still low. This happens because people process smoked flying fish using very simple technology and do not apply good and correct methods for smoking fish. The aim of implementing the smoking equipment in this activity is to provide training on how to use the fish smoking equipment properly and correctly as well as introduce the parts of the equipment and how to apply the smoking equipment using simple technological innovations to increase the maximum production of smoked fish. The fish smoking equipment training service activity was carried out on Saturday, August 26 2023, namely providing material in the sub-district office hall and applying the equipment in the Somba environment, Mosso Village. The method of activity carried out is counseling and training on how to apply the innovative flying fish smoking tool. This activity was attended by the Siamasei fish smoking group, which consists of 20 members. The result of this activity is that there is an increase in skills and the addition of new information and knowledge to the business partner group regarding the procedures for producing smoked flying fish products according to standard operating procedures (SOP) and standard sanitation operational procedures (SSOP) so that the group can produce processed fish products smoke of high quality and high selling value, and material on business management and marketing of flying fish smoking products, as well as on the application of simple technological innovations that can be used to improve the quality and quantity of flying fish smoking products. Apart from that, the business partner group was provided with knowledge related to better packaging of smoked fish products that have a longer shelf life. The training activities that have been carried out help the community in developing the flying fish processing business, increasing the quantity and quality of smoking production and with the presence of smoking equipment, it is hoped that the business partner group can increase sales value so that their welfare increases.